ASSESSMENT OF FUNCTIONAL OUTCOMES OF TREATMENT IN PATIENTS WITH STAGE III-IV OROPHARYNGEAL CANCER - Vasif V. Rakhmanov (Клінічна та профілактична медицина)
Introduction. Quality of life (QoL) studies in patients with oropharyngeal cancer can assist in formulating targeted treatment plans, optimising patient care, and improving follow-up strategies.